Isolation and Characterization of Antibiotic-Resistant Bacteria from Urinary Tract Infection on Diabetic Mellitus Patients - Kumar, M.; Prince, L. (Journal of Scientific Research, 2020)
Diabetes mellitus is a chronic disease-which occurs when the pancreas does not produce enough insulin, or when the body cannot effectively use the insulin it produces. This leads to an increased concentration of glucose in the blood (hyperglycemia). Diabetes mellitus is one of the most challenging health problems in India. The present study was investigated for isolation and characterization of antibiotic-resistant bacteria from urinary tract infection on diabetic mellitus patients. The 118 diabetic urine samples were collected and UTI bacteria using HiChrome UTI Agar was isolated. The diabetic UTI isolates were confirmed as Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus saprophyticus, Proteus mirabilis and Klebsiella aerogenes based on morphological and biochemical characteristics. Our study identified that almost all the bacteria were highly sensitive to Cefoperazone/Sulbactam (75/30 mcg), Gentamicin (10 mcg), Meropenem (30 mcg), Piperacillin/Tazobactam (100/10 mcg) and Nitrofurantoin (100 mcg) antibiotics. Interestingly Klebsiella aerogenes alone was found to be more resistant to the entire antibiotics used in this study. The antibiotic resistant Klebsiella aerogenes is one of the biggest treats to human health, antibiotic resistance occurs naturally, but misuse of antibiotics in humans is accelerating the process.